INFLUENCE OF CAPITAL ADEQUACY RATIO AND NON PERFORMING FINANCE ON PROFITABILITY (Case Study of Islamic Commercial Banks Registered with OJK 2014-2019) - Nuraeni, Nuraeni; Pradistya, Irvan Yoga (Jurnal Ekonomi Balance, 2020)
This study aims to determine the effect of Capital Adequacy Ratio and Non-Performance Finance on Return on Assets (Case Study of Islamic Commercial Banks registered with the Financial Services Authority in 2014-2019). The sample taken is 36 data taken from 2014 - 2019 with annual data on CAR, NPF, and ROA. The statistical methods used in this study are multiple regression analysis, Classical Assumption Test, Descriptive Statistical Analysis, Determination Analysis, and Hypothesis Testing. From the results of this study, it is known that partially the Capital Adequacy Ratio has no effect on Return on Assets because the t count value is smaller than the t table (0.096 <2.034) the significance value is greater than 0.05 (0.096> 0.05) while non-performing Finance on Return on Assets has a negative and significant effect because the t value is smaller than the t table (-3.553 <2.034) and the significance value is less than 0.05 (0.001 <0.05). And simultaneously the Capital Adequacy Ratio and Non-Performance Finance have a joint effect on Return on Assets because the calculated f value is greater than f table (9,341> 3.28) and the significance value is less than 0.05 (0.001 <0.05).